The Impact of Modern Innovative Educational Technologies for The Environmental Education of Students with Hearing Impairments - Abdullaeva, Gavhar; Aydarov, Erkin (International Journal of Psychosocial Rehabilitation, 2020)
Innovative technologies in teaching children with special educational needs occupy an important place in the educational process, since they contribute to the implementation of the students’ ecological culture. The use of gaming technology stimulates the cognitive activity of children, an independent search for answers to questions; allows you to enjoy the children’s life experiences, including their everyday ideas about something. Game technologies create great opportunities for the formation of an information culture in children with the help of information and communication technologies in the educational process.